دراسة القواعد النحوية عن وظائف قضية الواو في سورة يس - Muh. Abrar; Asriani Abdullah; Usman Syafrudin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
Waw is the 27th letter of the alphabet. It is public and more like the middle letters. Its exits from the statement of the first tongue and the middle of the upper palate, its origin and Yo, are likely to be replaced by J. And be in the original words as the word was promised, and extra as in the word Mansour, and instead as in the word is authorized. Types of waws include: waw oath, waw (lord), waw (with), waw that focuses the present tense, waw emotion, waw appeals, waw alwaw, waw o8, waw male pronoun or waw group, wow by the raised sign, waw male pronoun or F group. By this message, it is easy for us to understand and study waw in general Waw in Surat Yassin in particular. The researcher found 166F in Surat Yassin, including: 1F Al-Qasim, 52F, Kindness, 24F, Appeals, 5F, Status, 17F with mark of lifting, 67F, Conscience.